High Expression of miR-204 in Chicken Atrophic Ovaries Promotes Granulosa Cell Apoptosis and Inhibits Autophagy - Cui, Zhifu; Liu, Lingbin; Kwame Amevor, Felix; Zhu, Qing; Wang, Yan; Li, Diyan; Shu, Gang; Tian, Yaofu; Zhao, Xiaoling (Frontiers in Cell and Developmental Biology, 2020)
Atrophic ovary implies a decrease in the ovarian tissue volume and maybe indicative of ovarian failure, tumor or interrupted ovarian blood supply, which may therefore affect reproduction in chicken. Ovarian tumor is accompanied by an increase in follicular atresia, granulosa cell apoptosis and autophagy. In this study, we found that miR-204 was highly expressed in chicken atrophic ovaries, therefore we investigated its function on granulosa cell (GC) apoptosis and autophagy in chickens. We found that overexpression of miR-204 reduced mRNA and protein levels of proliferation-related genes and increased apoptosis-related gene expression. Cell counting kit-8 (CCK-8), 5-ethynyl-2-deoxyuridine (EdU) assay, and flow cytometry showed miR-204 inhibited the proliferation of chicken GCs and promoted apoptosis. Further, we confirmed from Luciferase assay that forkhead box K2 (FOXK2) (downstream regulator of PI3K/AKT/mTOR signal pathways) was directly targeted by miR-204, thereby promoting the proliferation and inhibiting apoptosis of chicken GCs. miR-204 was found to be involved in autophagy of GC by targeting transient receptor potential melastatin 3 (TRPM3). The luciferase activities of the two binding sites of TRPM3 were decreased with response to miR-204 mimic and the autophagic flux was increased after miR-204 inhibition. However, overexpression of miR-204 produce opposite results in autophagosomes and autolysosomes. Subsequently, we demonstrated that miR-204 inhibits granulosa cell autophagy by suppressing protein expression of TRPM3/AMPK/ULK signaling pathway. miR-204 inhibition enhanced autophagy by accumulating and degrading the protein levels of LC3-II (microtubule-associated protein light chain 3B) and p62 (protein of 62 kDa), respectively. Meanwhile, miR-204 overexpression showed contrary results. Immunofluorescence analysis showed a significant reduction in the fluorescence intensity of LC3B, whereas p62 protein was increased after TRPM3 silencing. Generally, these results indicated that miR-204 was highly expressed in chicken atrophic ovaries, which promoted granulosa cell apoptosis via repressing FOXK2 through PI3K/AKT/mTOR pathway, and inhibited autophagy by impeding the TRPM3/AMPK/ULK pathway.